SOCIAL PRESENCE, COLLABORATION, ACADEMIC PERFORMANCE, AND STUDENT AND FACULTY SATISFACTIONS IN COVID-19-INDUCED ONLINE DISTANCE LEARNING - Pael, Kenneth (English Study Program University of Pasir Pengaraian, 2024)
This study investigated the existing levels of social presence, collaboration, academic performance, and student and faculty satisfactions and their relationships in the online distance learning (ODL) environment during the COVID-19 pandemic. Three hundred ninety-seven (397) students (male, n = 134; female, n = 263) and 253 faculty (male, n = 112; female, n = 141) from eight higher education institutions in Dumaguete City, Philippines, participated in the study. Data from the respondents were collected through online questionnaires and analyzed using descriptive and correlational statistics. The results revealed that the students gathered high levels of social presence (wx = 3.57, SD = 0.61), collaboration (wx = 3.97, SD = 0.55), and student satisfaction (wx = 3.56; SD = 0.67) in ODL. Consequently, moderate levels of academic performance (wx = 3.26, SD = 0.53) and faculty satisfaction (wx = 3.10, SD = 0.39) were perceived by the students and faculty, respectively. Furthermore, Spearman’s rho correlation found that there were statistically significant relationships between social presence and collaboration (r = 0.56, p = <0.000001), collaboration and student satisfaction (r = 0.57, p = <0.000001), and social presence and student satisfaction (r = 0.70, p = 0.0000005). Moreover, student satisfaction and academic performance had a strong positive correlation (r = 0.80, p = <0.000001). Lastly, through the Mann-Whitney U test, faculty satisfaction did not have any significant relationship with student satisfaction (z = 9.23, p = <0.0001) and academic performance (z = 4.81, p = <0.0001).